Association between socioeconomic status and Parkinson's disease: findings from a large incident case–control study. Issue 1 (15th February 2023) - Najafi, Fereshteh; Mansournia, Mohammad Ali; Abdollahpour, Ibrahim; Rohani, Mohammad; Vahid, Farhad; Nedjat, Saharnaz
Abstract : Introduction: The association between socioeconomic status (SES) and Parkinson's disease (PD) has been investigated in few studies. To our knowledge, SES measurement based on wealth index and perceived SES in PD patients has not been investigated in any study. Also, the simultaneous measurement of objective and perceived SES and their association with PD has not been conducted yet. This study aimed to determine the association between various SES indicators and PD. Methods: This incident case–control study was conducted on 508 patients with PD and 1015 controls randomly selected from the general population in Iran in 2021–2022. A telephone interviewing method was used for data collection. The wealth index and educational level were used to measure objective SES. Perceived SES was also recorded. Multiple logistic regression was used to calculate the adjusted OR (AOR). Results: A significant association based on the wealth index was found, where the intermediate category had lower odds of developing PD than the deprived category (AOR 0.75 (95% CI 0.58 to 0.99)). The odds of PD was significantly higher in the people with academic education compared with illiterate and primary-level education (AOR 2.17 (95% CI 1.58 to 2.99). Additionally, the odds of PD were significantly lower in the intermediate (AOR 0.26 (95% CI 0.13 to 0.52)) and affluent (AOR 0.21 (95% CI 0.11 to 0.40)), compared with the deprived categories based on perceived SES. Similar results were obtained in the analysis by sex. Conclusion: This study demonstrated that lower wealth index, a lower perceived SES and academic education are associated with increased the odds of PD.